Optimal placement of high-channel visual prostheses in human retinotopic visual cortex - van Hoof, Rick; Lozano, Antonio; Wang, Feng; Klink, P. Christiaan; Roelfsema, Pieter R.; Goebel, Rainer (Institute of Physics, 2025)
Objective. Recent strides in neurotechnology show potential to restore vision in individuals with visual impairments due to early visual pathway damage. As neuroprostheses mature and become available to a larger population, manual placement and evaluation of electrode designs become costly and impractical. An automatic method to simulate and optimize the implantation process of electrode arrays at large-scale is currently lacking. Approach. Here, we present a comprehensive method to automatically optimize electrode placement for visual prostheses, with the objective of matching predefined phosphene distributions. Our approach makes use of retinotopic predictions combined with individual anatomy data to minimize discrepancies between simulated and target phosphene patterns. While demonstrated with a 1000-channel 3D electrode array in V1, our simulation pipeline is versatile, potentially accommodating any electrode design and allowing for design evaluation. Main results. Notably, our results show that individually optimized placements in 362 brain hemispheres outperform average brain solutions, underscoring the significance of anatomical specificity. We further show how virtual implantation of multiple individual brains highlights the challenges of achieving full visual field coverage owing to single electrode constraints, which may be overcome by introducing multiple arrays of electrodes. Including additional surgical considerations, such as intracranial vasculature, in future iterations could refine the optimization process. Significance. Our open-source software streamlines the refinement of surgical procedures and facilitates simulation studies, offering a realistic exploration of electrode configuration possibilities.
Keywords: electrode placement; intracortical electrodes; magnetic resonance imaging; neurotechnology; phosphene mapping; primary visual cortex; visual neuroprosthetics; Biomedical Engineering; Cellular and Molecular Neuroscience